Climate Change Effects On Aquaculture Production Performance In Malaysia: An Environmental Performance Analysis - Rosita, Hamdan; Azmah, Othman; Fatimah, Kari (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study identifies the effects of climate variability as an environmental pressure on aquaculture production in Malaysia. Using Malmquist index approach, the analyses were applied to brackish-water ponds and cage aquaculture sectors in six states in Malaysia from 1993 to 2013. The Dynamic Malmquist Data Envelopment Analysis results had reflected that environmental technical change is the main factor behind the improvement of environmental performance index in pond production while the relative eco-efficiency is the major influencing factor in environmental performance index in cage aquaculture. Moreover, Pahang is the most efficient states in environmental aspects and technical support of brackish-water aquaculture ponds and cage activities, while Selangor is the least efficient state in aquaculture activities and under high climate change risks.